Water withdrawal and consumption reduction for electrical energy generation systems. (15th August 2019) - Nouri, Narjes; Balali, Farhad; Nasiri, Adel; Seifoddini, Hamid; Otieno, Wilkistar
Highlights: A model is presented to minimize the amount of water consumed by the energy sector. The model dispatches the generation-cooling mix to quantify water consumption. Electricity demand in California needs a minimum of 58, 673 cubic meters of water. 16% reduction in the California electricity usage cuts the water consumption by 94%. No hydro generation in California reduces water consumption by 61%. Abstract: Water is the greatest resource for life on earth. Various human activities affect the quality and quantity of this precious resource, and there are many initiatives to ensure water resources are protected from overuse, pollution, and industrial and agricultural waste. Since the energy sector is the second largest consumer of water after agriculture, water and energy systems are highly interlinked. Specifically, a significant amount of water is used in the energy generation process primarily for producing steam and for cooling processes, the water used for cooling processes will be returned back to the reservoir. Consequently, most fossil-based power plants in addition to consuming water, impact the water resources by raising the temperature of water withdrawn for cooling. Limited water resources can also affect the ability to generate electric power to meet the demand. Therefore, integrated planning for the interleaved energy and water sectors is essential for both water and energy savings. This paper describes a comprehensive study that analyzes and quantifies water withdrawals and consumption of various electricity generation sources such as coal, natural gas and renewable sources. The study has developed a general model to determine the water consumption and impact for various energy generation scenarios and to minimize the amount of water consumption while considering several limitations and restrictions. A case study performed for the state of California indicates that quantification of water consumption can be formulated and potential opportunities for water saving can be identified.